Pengaruh Sektor Unggulan Terhadap Pertumbuhan Ekonomi Kabupaten Mimika Tahun 2019-2023 (Analisis LQ Dan DLQ) - Kondo, Sri Sofia; Pentury, Merlin; Fahrunnisa , Lutfiana; Narew , Ignasius (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Mimika Regency is a district that is famous for having the largest gold mine in the world owned by PT. Freeport Indonesia. Economic growth in Mimika Regency is still relatively low when compared to every district city in Papua, this is due to changes in the amount of production of goods and services which results in economic growth not growing well. The purpose of this study is to find out the leading sectors and which provide the greatest competitiveness in Mimika County. This study uses secondary data, namely GDP (Gross Regional Domestic Product) which is quantitative in nature with Location Quotient (LQ) analysis methods and Dynamic Location Quotient analysis. The results of the Location Quotient (LQ) analysis show that of the 17 economic sectors in Mimika Regency, there is 1 economic sector that is the leading sector, while the Dynamic Location Quotient Results show that of the 17 economic sectors, there are 6 prospective sectors and 11 non-prospective sector